A witch's life in Mongol. 1 - Tomato Soup (Yen Press, 2025)
"Eight centuries ago, in the latter days of the Islamic golden age, a young girl arrived in the Khwarazmian city of Tus. She was a slave. But she learned.Eight centuries ago, the Mongols blazed across the map, swept Khwarazm into the ash heap of history, and took all they desired from the ruins. They took the girl who learned.So begins the true story of how a "witch," wielding knowledge as her only weapon, came to hold the greatest empire the world has ever known in the palm of her hand..."--back cover.